2016
DOI: 10.1109/tpwrs.2015.2390132
|View full text |Cite
|
Sign up to set email alerts
|

Neural Network-Based Model Design for Short-Term Load Forecast in Distribution Systems

Abstract: Accurate forecasts of electrical substations are mandatory for the efficiency of the Advanced Distribution Automation functions in distribution systems. The paper describes the design of a class of machine-learning models, namely neural networks, for the load forecasts of medium-voltage/low-voltage substations. We focus on the methodology of neural network model design in order to obtain a model that has the best achievable predictive ability given the available data. Variable selection and model selection are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
75
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(83 citation statements)
references
References 41 publications
2
75
0
Order By: Relevance
“…Previous work has shown that classic feedforward ANN may provide outstanding results in time series prediction tasks [7,[10][11][12][13][14]24,25]. In this study, we have selected two neural network architectures aimed specifically at this problem to be used as prediction models for energy consumption.…”
Section: Methodsmentioning
confidence: 99%
“…Previous work has shown that classic feedforward ANN may provide outstanding results in time series prediction tasks [7,[10][11][12][13][14]24,25]. In this study, we have selected two neural network architectures aimed specifically at this problem to be used as prediction models for energy consumption.…”
Section: Methodsmentioning
confidence: 99%
“…We can conclude that GRU neural networks do better in both convergence speed and training time, which depends on the improved single structure of GRU units. We also performed the experiments to compare with current methods such as back-propagation neural networks (BPNNs) [7,8], stacked autoencoders (SAEs) [17], RNNs [24,25], and LSTM [29][30][31]. Their parameters and structures are set as described in Section 3.2.…”
Section: Comparison Of Results Of Proposed Methodsmentioning
confidence: 99%
“…Besides, the response time of load demand to temperature changes is larger than that of the sampling period. Therefore the average temperature of the past 3 h (Tav(3)), 6 h (Tav(6)), and 24 h (Tav (24)) are selected as temperature variables [40]. (1) Historical load.…”
Section: Feature Set Constructionmentioning
confidence: 99%